A Review of Geodetic Datums of Nepal and Transformation Parameters for WGS84 to Geodetic Datum of Nepal - Manandhar, Niraj (Journal on Geoinformatics, Nepal, 2017)
In Nepal there exist different coordinate systems based on different geodetic datum. The existence of these datum and coordinate systems are poorly known. In this literature the geodetic datum that is in existence in one way or other are illustrated and discussed. The next common problem encountered by users is the availability of authentic precise transformation parameter between National geodetic datum and World Geodetic Datum 1984 (WGS84) ; global datum used by global positioning system (GPS). There can exist a considerable difference in the position between local and the global system and the difference could be of several hundred meters. Based on the availability of data three sets of transformation parameters has been determined. The tests have been carried out to evaluate the accuracy of the transformation parameter in this region. The transformation parameter is recommended to transform the topographical data base of scale 1: 3500 and smaller. The accuracy of the transformation parameters are specified and can be used accordingly. This study will ultimately provide standardization and ease in transforming the coordinates from global datum (WGS84) to national geodetic datum of Nepal and vice versa. Nepalese Journal on Geoinformatics, Vol. 14, 2015, page:4-7